Type-1 Grade 2 Multi-Focal Gastric Neuroendocrine Tumors Secondary to Chronic Autoimmune Gastritis - Yu, Ziqi; Wang, Aiyao; Hu, Chong; Yu, Tao; Chen, Jianyong (Frontiers in Medicine, 2022)
Background Chronic autoimmune gastritis (CAG) refers to the chronic atrophic gastritis due to autoimmunity. Loss of gastric glands in CAG results in the hypergastrinemia and achlorhydria leading to Vitamin B12 deficiency and hyperplasia of G cells and enterochromaffin-like (ECL) cells. Vitamin B12 deficiency could cause pernicious anemia and subacute combined degeneration, while G cells and ECL cells hyperplasia might develop gastric neuroendocrine tumor (G-NET). Case presentation A 35-year-old Chinese female who presents multi-focal type-1 Grade 2 (G2) NETs with a 14-year history of pernicious anemia and subacute combined degeneration. Conclusion Here, we report a rare case of a Chinese patient presenting G-NET combined with pernicious anemia and subacute combined degeneration, which are secondary to chronic autoimmune gastritis. This case also illustrates the importance of routine gastroscopy in patients with unknown reason of Vitamin B12 deficiency.